Five New Diarylbutyrolactones and Sesquilignans from Saussurea medusa and Their Inhibitory Effects on LPS-induced NO Production - Cao, Jing-Ya; Wang, Zhi-Yao; Stewart, Alan J.; Dong, Qi; Zhao, Ye; Mei, Li-Juan; Tao, Yan-Duo; Yu, Rui-Tao (Planta Medica, 2023)
Five new diarylbutyrolactones and sesquilignans (1a/1b – 4), including one pair of enantiomers (1a/1b), together with 10 known analogues (5 – 14), were isolated from the whole plants of Saussurea medusa. Compound 1 was found to possess an unusual 7,8′-diarylbutyrolactone lignan structure. Separation by chiral HPLC analysis led to the isolation of one pair of enantiomers, (+)-1a and (−)-1b. The structures of the new compounds were elucidated by extensive spectroscopic data. All compounds, except compounds 5, 7 and 9, were isolated from S. medusa for the first time. Moreover, compounds 1 –  4, 8 and 10 – 14 had never been obtained from the genus Saussurea previously. Compounds (+)- 1a, 2, 5, 7, and 9 – 11 were found to inhibit the lipopolysaccharide (LPS)-induced release of NO by RAW264.7 cells with IC50 values ranging from 10.1 ± 1.8 to 41.7 ± 2.1 µM. Molecular docking and iNOS expression experiments were performed to examine the interactions between the active compounds and the iNOS enzyme.
Keywords: Saussurea medusa; Asteraceae; diarylbutyrolactone lignan; sesquilignan; anti-inflammatory activity; molecular docking